The Serbuk Kayu sebagai Penurun Kadar Amonia pada Instalasi Pengolahan Air Limbah Puskesmas - Nawan Prianto; Prihantoro; Zahra Aulia (Buletin Keslingmas, 2026)
Wastewater generated from healthcare facilities such as health centers contains various pollutants, including ammonia (NH₃), which can potentially pollute the environment. This study aims to determine the effectiveness of activated charcoal made from sawdust as a filtration medium in reducing ammonia levels in the Wastewater Treatment Plant (WWTP) at Sukadamai Inpatient Health Center. This research is an experimental study using a pretest-posttest design without a control group. The filtration media were created using activated charcoal derived from sawdust that had undergone carbonization and activation with H₃PO₄ solution. The variations in media thickness used were 100 cm, 110 cm, and 120 cm. Filtration was carried out using a vertical flow (downflow) system with different contact times. The tested parameters included ammonia levels, pH, and temperature. The results showed that activated sawdust charcoal significantly reduced ammonia levels. Variations in media thickness affected the filtration effectiveness, with the 120 cm thickness yielding the best ammonia reduction compared to the others. It can be concluded that activated sawdust charcoal has potential as an effective, low-cost, and environmentally friendly alternative media for reducing ammonia levels in wastewater from health centers. This study is expected to serve as a reference for the development of small-scale wastewater treatment systems.